Superior Mesenteric Artery Syndrome: A Misdiagnosed Disorder - Zakia El Yousfi MD; Ismail Mohamed Halfi MD; Salma El Houss MD; Nazik Allali PhD; Siham El Haddad PhD; Latifa Chat PhD (SAGE Publishing, 2024)
The superior mesenteric artery syndrome also known as Wilkie's syndrome or Benign duodenal stasis, is a condition that occurs when the third duodenum is compressed between the superior mesenteric artery anteriorly and the abdominal aorta posteriorly following the disappearance of the perivascular fatty tissue. It can emulate the symptoms of an upper abdominal obstruction. This case involves a 9-year-old female patient experiencing food vomiting that did not improve with medication. Radiological work-up, which included an abdominal X-ray and a CT angiography, led to the diagnosis of extrinsic and incomplete obstruction of the third duodenum by the aorto-mesenteric clamp. Unfortunately, this diagnosis is rarely made. The purpose of this article is to provide a review of the etiology, clinical presentation, and imaging findings of this syndrome.